2002
DOI: 10.1136/oem.59.9.643
|View full text |Cite
|
Sign up to set email alerts
|

Chrysotile and tremolite asbestos fibres in the lungs and parietal pleura of Corsican goats

Abstract: Background and Aims:Environmental exposures to chrysotile and tremolite from the soil cause pleural plaques and mesothelioma in northeast Corsica. Goats grazing in the contaminated areas inhale asbestos fibres. We used this natural animal model to study whether these exposures actually result in increased fibre burdens in the lungs and parietal pleura.Methods:Ten goats from areas with asbestos outcrops and two from other areas were slaughtered. Fibre content of lung and parietal pleural samples was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…Tremolite fi bers have been detected in the parietal pleura of one dog and two goats that lived in some areas of Corsica where there are outcropping serpentinitic rocks bearing this material (Rey et al 1993). Comparable results have been obtained from goats that lived in areas contiguous to those described above (Dumortier et al 2005). The concentrations are lower than those detected in occupationally exposed humans.…”
Section: Amphiboles In Animal Lungssupporting
confidence: 72%
“…Tremolite fi bers have been detected in the parietal pleura of one dog and two goats that lived in some areas of Corsica where there are outcropping serpentinitic rocks bearing this material (Rey et al 1993). Comparable results have been obtained from goats that lived in areas contiguous to those described above (Dumortier et al 2005). The concentrations are lower than those detected in occupationally exposed humans.…”
Section: Amphiboles In Animal Lungssupporting
confidence: 72%
“…From 1963 to 1985 in Upsala, Sweden, 1,598 men with pleural plaques were studied and it was found that relevant risk of developing lung cancer amounted to 1.4% while 9 cases of mesothelioma were diagnosed, compared to the 0.8 expected [Hillerdal, 1994]. The kind of the fibers (amphibole group, especially tremolite) plays an important role not only in the appearance of pleural plaques but also of mesothelioma caused by asbestos environmental exposure [Sichletidis et al, 1992b;Dumortier et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…There has been no active asbestos mining or related industry in Sivas. In another study, Dumortier et al [26] found tremolite and chrysotile asbestos fibers in the lungs of goats grazing on ophiolitic belts in Corsica. The risk of developing malignant mesothelioma or pleural plaques was halved by every additional 5-km distance of the birthplace from ophiolites.…”
Section: Key Pointsmentioning
confidence: 93%